Day hospital versus intensive outpatient mentalization-based treatment: 3-year follow-up of patients treated for borderline personality disorder in a multicentre randomized clinical trial. Issue 3 (30th June 2020) - Smits, Maaike L.; Feenstra, Dine J.; Bales, Dawn L.; Blankers, Matthijs; Dekker, Jack J. M.; Lucas, Zwaan; Kamphuis, Jan H.; Busschbach, Jan J. V.; Verheul, Roel; Luyten, Patrick
Abstract: Background: Two types of mentalization-based treatment (MBT), day hospital MBT (MBT-DH) and intensive outpatient MBT (MBT-IOP), have been shown to be effective in treating patients with borderline personality disorder (BPD). This study evaluated trajectories of change in a multi-site trial of MBT-DH and MBT-IOP at 36 months after the start of treatment. Methods: All 114 patients (MBT-DH n = 70, MBT-IOP n = 44) from the original multicentre trial were assessed at 24, 30 and 36 months after the start of treatment. The primary outcome was symptom severity measured with the Brief Symptom Inventory. Secondary outcome measures included borderline symptomatology, personality and interpersonal functioning, quality of life and self-harm. Data were analysed using multilevel modelling and the intention-to-treat principle. Results: Patients in both MBT-DH and MBT-IOP maintained the substantial improvements made during the intensive treatment phase and showed further gains during follow-up. Across both conditions, 83% of patients improved in terms of symptom severity, and 97% improved on borderline symptomatology. No significant differences were found between MBT-DH and MBT-IOP at 36 months after the start of treatment. However, trajectories of change were different. Whereas patients in MBT-DH showed greater improvement during the intensive treatment phase, patients in MBT-IOP showed greater continuing improvement during follow-up. Conclusions: Patients in both conditions showed similar large improvements over the course of 36 months, despite large differences in treatment intensity. MBT-DH and MBT-IOP were associated with different trajectories of change. Cost-effectiveness considerations and predictors of differential treatment outcome may further inform optimal treatment selection.